(This) is Not My Water Bottle: Gender Discourse Analysis of DepEd English 1-3 Textbooks - Baygan, Maria Araceli M. (Alipato, A Journal of Basic Education; Vol 14 (2023), 2024)
Textbooks, when used by children in their formative years, are sources of symbolic models, who they identify with and from whom they learn what they perceive as socially accepted behavior. This research analyzes four Department of Education (DepEd) K-12 English textbooks for Grades 1 to 3. It aims to identify gender representations as constructed in the textbooks with the use of Sara Mills’ Feminist Stylistics Analysis and Kress and Van Leeuwen’s Multimodality Theory. The two theories were used as supplements in order to identify gender construction as portrayed by the materials’ linguistic and non-linguistic resources. Through careful analysis, the research found strong gendering in professions (e.g., doctors, cops are males; nurses, teachers are females) and in division of household tasks (mothers as caretakers; fathers as providers). Illustrations in the materials were found to play a huge role in and heavily impact gender construction in the materials. For example, a seemingly non-gendered sentence, “This is not my water bottle” is shown to exhibit gender bias due to its accompanying illustration (a flower drawn on the water bottle). Change in the DepEd guidelines for textbook evaluation, particular to gender, is suggested to aid the DepEd, publishers, and other content producers to assess and ensure gender-sensitivity in textbooks.